Profile of chlidren inflicted with primary humoral immunodeficincy disorders - Nesreen Ibrahim Eldesouky; Mariam Halim Yacoub; Nermeen Mouftah Galal; Sherif Gamil Waly (Cairo : Nesreen Ibrahim Eldesouky, 2010)
Agammaglobulinemia or hypogammaglobulinemia is the most common of primary immunodeficiency disorders patients have recurrent infections in upper and lower respiratory tract gastrointestinal tract and also affecting other systems primary immunodeficiency disorders may have very subtle presentations early in life and need a high index of suspicion to be picked up
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Pediatrics; Primary immunodeficincy disorders